A Companion to José Enrique Rodó / Gustavo San Roman - San Román, Gustavo, 1956- (Monografías A., 2018)
This Companion to José Enrique Rodó (1871-1917) is the first comprehensive intellectual biography in English of the great Latin Americanist, stylist, and writer on the ethical and aesthetic development of the youth of his subcontinent. Rodó is best known for his essay Ariel (1900), which marked the consolidation of modernity in Latin America in the wake of mass immigration and Spain's crushing defeat at the hands of a United States that was impressing upon its southern neighbours the unequivocal signs of its might. The circumstances were therefore most propitious for reflection on what being Latin American meant; Ariel did precisely that, as it pondered "roots" and proposed future "routes". The book provides, in chronological order, a detailed and up-to-date assessment of Rodó's writings, his context and legacy, both immediate (during the period of arielismo) and current, and draws widely on unpublished material from the extensive archives of his papers held in Montevideo. As befits its subject matter, the book's aim has been idealistic: to cover all relevant aspects of Rodó's work in order to give the fullest possible account of his worldview, including hitherto little-explored areas that shed new light on it, notably the relationship between his philosophical stance, religion and politics. Gustavo San Román is Professor of Spanish at the University of St Andrews.